PERENCANAAN HUTAN KOTA REKREASI MANGROVE DI WILAYAH PESISIR KECAMATAN KUTA RAJA, KOTA BANDA ACEH, PROPINSI NAD - Noviyati Valentina S; Siti Nurisjah (Jurnal Lanskap Indonesia, 2010)
The study was located in Kuta Raja Sub-District, Banda Aceh City, Nanggroe Aceh Darussalam Province. The site is coastal areawhich was directly affected by eartquake and tsunami disaster that caused environmental degradation and significantly reduced the area of land.The area of site planning is 316.65 Ha, covers 78.76 Ha of Gampong Jawa Village, 211.24 Ha of Gampong Pande Village, and 26.65 Ha of Peulanggahan Village. The site has unique character of coastal area with clay soil and flat topography,and consisted of land and inundated areas. Ecological concept has been applied to the forest, with aim to improve environmental quality of the city after tsunami. Besides, the urban forest is hopefully indirectly able to protect the land area behind, and also as recreational areafor urban communities.